Answer:
0.143059384
Step-by-step explanation:
=> ![\frac{\sqrt{19+6^2} }{7.2^2}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B19%2B6%5E2%7D%20%7D%7B7.2%5E2%7D)
=> ![\frac{\sqrt{19+36} }{51.84}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B19%2B36%7D%20%7D%7B51.84%7D)
=> ![\frac{\sqrt{55} }{51.84}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B55%7D%20%7D%7B51.84%7D)
=> ![\frac{7.416}{51.84}](https://tex.z-dn.net/?f=%5Cfrac%7B7.416%7D%7B51.84%7D)
=> 0.143059384
Answer:
anwser -10000 n
Step-by-step explanation:
You have a 300 feet side length square and you need to calculate the length of the diagonal. When you split the square along one diagonal you get triangles, so you can apply Pythagoras' Theorem, with the hypotenuse as the needed diagonal.
a²+b²=c²
300²+300²=c²
2*300²=c²
√(2*300²)=c
√(2) * √(300²)=c
√(2) * 300=c
c~424.26 ft which is the solution/option c
Answer: 18 yellow flowers
Step-by-step explanation:
There are 9 flowers in each of the 6 rows. The total number of flowers planted is therefore:
= 6 rows * 9 flowers per row
= 54 flowers
A 1/3 of these flowers were yellow flowers so the number of yellow flowers planted is:
= 1/3 * 54
= 54/3
= 18 yellow flowers
Answer:
Step-by-step explanation:
Given the expression
![\frac{7}{3}\:-\:\frac{2}{3}\:+\:v^3\:-\:3v^3](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B3%7D%5C%3A-%5C%3A%5Cfrac%7B2%7D%7B3%7D%5C%3A%2B%5C%3Av%5E3%5C%3A-%5C%3A3v%5E3)
solving the expression
![\frac{7}{3}\:-\:\frac{2}{3}\:+\:\sqrt{3}-3\sqrt{3}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B3%7D%5C%3A-%5C%3A%5Cfrac%7B2%7D%7B3%7D%5C%3A%2B%5C%3A%5Csqrt%7B3%7D-3%5Csqrt%7B3%7D)
combine the fractions i.e ![\frac{7}{3}-\frac{2}{3}=\frac{5}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B3%7D-%5Cfrac%7B2%7D%7B3%7D%3D%5Cfrac%7B5%7D%7B3%7D)
![\frac{7}{3}\:-\:\frac{2}{3}\:+\:\sqrt{3}-3\sqrt{3}=\frac{5}{3}+\sqrt{3}-3\sqrt{3}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B3%7D%5C%3A-%5C%3A%5Cfrac%7B2%7D%7B3%7D%5C%3A%2B%5C%3A%5Csqrt%7B3%7D-3%5Csqrt%7B3%7D%3D%5Cfrac%7B5%7D%7B3%7D%2B%5Csqrt%7B3%7D-3%5Csqrt%7B3%7D)
add similar elements i.e ![\sqrt{3}-3\sqrt{3}=-2\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D-3%5Csqrt%7B3%7D%3D-2%5Csqrt%7B3%7D)
Thus,